Kecerdasan Emosional dalam Novel Bukan Pasar Malam Karya Pramoedya Ananta Toer: Relevansinya bagi Pembelajaran Sastra SMA: Emotional Intelligence in Pramoedya Ananta Toer's Novel Bukan Pasar Malam: Its Relevance for High School Literature Learning - Hanif Murfid Hidayat; Dian Hartati; Wienike Dinar Pratiwi; Kurnia Dewi Nurfadilah (JBSI: Jurnal Bahasa dan Sastra Indonesia, 2026)
The lack of emotional intelligence in adolescents makes them have difficulty recognizing and controlling their feelings, experience stress easily, neglect their responsibilities, lack empathy, and tend to solve problems arrogantly. Therefore, this research is important for training adolescents, especially students, to hone their self-awareness skills. This study aims to describe the values of emotional intelligence in Pramoedya Ananta Toer's novel Bukan Pasar Malam and its relevance to literature learning in high school. The method used in this research is qualitative descriptive. The subject of this research is Pramoedya Ananta Toer's novel Bukan Pasar Malam, and the object of research is the emotional intelligence aspects contained in the novel. Data collection for this research was conducted using reading and note-taking. Data analysis involved data collection, data reduction, data presentation, and conclusions. The research data are presented as paragraph quotations or dialogues. The results of this study indicate that there are five main aspects of social intelligence that students can emulate. This research has relevant results for literature learning in high school. Through this novel appreciation activity, students can recognize themselves, manage emotions, be responsible, empathize, and maintain harmonious social relationships. Thus, literary works function as an effective medium for training students' emotional intelligence.